PENGARUH FORMULASI KOMPOS TANDAN KOSONG KELAPA SAWIT DENGAN PUPUK NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays. L Var Saccarata Sturt) - Kurniawan, Elis; ', Murniati; ', Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Sweet corn has economic value and high sale value, because it tastes good and sweet so it greatly favored by the people. The old plant early maturing and ready to be harvested 70 days after planting. The aim of this research are to determine the effect of formulation compost TKKS with NPK fertilizer on the growth and production of sweet corn (Zea mays. L Var Saccarata Sturt)and determine the best formulation that could improve result and production. Research wasconducted atthe Faculty ofAgriculture, University ofRiau, fromMarch toMay 2014. The study conducted using completely randomized design(CRD), whichconsists of8 treatments, eachtreatment was repeated4 timesto obtain32units oftrial,Each experimental unit consisted of 24 plants, 5 plants taken at random.The observed parameters are ratio of the root crown, dry plant weight, when the pistil appear, when the pollen arise, cob length without cornhusk, cobs diameters without cornhusk and weight of cobswithout cornhusk / plot. Results of analysis of variance continued with DuncanNew Multiple Range test at 5 %. Fromresults of the research that has been conducted shows formulation compost TKKS with NPK no real effect on all parameters. formulation compost10 ton/ha +75 kg/ha NPKgive the relatively best results on the growth and yield of sweet cornthan other treatments. Keywords: Sweet corn, composts TKKS and fertilizer NPK